2024
DOI: 10.3390/chemosensors12030043
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Decorated ZnO Hexagonal Microdiscs for NH3 Sensor

Yi Li,
Boyu Zhang,
Juan Li
et al.

Abstract: The NH3 sensor is of great significance in preventing NH3 leakage and ensuring life safety. In this work, the Pd-decorated ZnO hexagonal microdiscs are synthesized using hydrothermal and annealing processes, and the gas sensor is fabricated based on Pd-decorated ZnO hexagonal microdiscs. The gas-sensing test results show that the Pd-ZnO gas sensor has a good response to NH3 gas. Specifically, it has a good linear response within 0.5–50 ppm NH3 at the optimal operating temperature of 230 °C. In addition, the Pd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…The nature of the second peak is more disputable. Commonly, it is attributed to oxygen vacancies in ZnO nanoparticles [16,57], which, if located on the surface of the ZnO nanoparticles, form dangling bonds. However, Frankcombe et al found this to be a misinterpretation, instead attributing the spectral component at these BEs to the OH-related species [58].…”
Section: Core-level Studies Of the Amg And Am-znomentioning
confidence: 99%
“…The nature of the second peak is more disputable. Commonly, it is attributed to oxygen vacancies in ZnO nanoparticles [16,57], which, if located on the surface of the ZnO nanoparticles, form dangling bonds. However, Frankcombe et al found this to be a misinterpretation, instead attributing the spectral component at these BEs to the OH-related species [58].…”
Section: Core-level Studies Of the Amg And Am-znomentioning
confidence: 99%
“…The response time and recovery time of the sensor were defined as the time to attain 90% of the maximum response value and the time to return back to 10% of the total response value (as illustrated in Figure S3). The relative humidity (RH) value in the test chamber is controlled by mixing dry and humidity gases via mass flow meters. , The humidity gas is obtained by filling a N 2 gas flow through different saturated salt solutions.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The resistances in air (R a ) and in the presence of the target gas (R g ) were measured constantly, and the sensor response was calculated as R = R g /R a for NO 2 gas and vice versa for reducing gases. Additionally, the response time (τ res ) and recovery time (τ rec ) were defined as the times required for the resistance to reach its 90% final value after injection and stoppage of NO 2 gas, respectively [48]. During the gas sensing tests, the relative humidity (RH) in the chamber was 30% at RT.…”
Section: Gas Sensing Testsmentioning
confidence: 99%